VIDEOS ANIMATION TO LEARNING - Nurmayanti; Mohammad Ahmad Bani Amer (International Journal of Teaching and Learning, 2023)
Based on the results of research regarding the effect of using animated videos on the science learning outcomes of class VIII students at SMP Negeri 2 Pancarijang can concluded as follows: The use of animated videos in the teaching and learning process has an influence on the science learning outcomes of class VIII students at SMPN 2 Pancarijang. From the results of the average value found, it shows that there is influence usage videos animation to results Study Science class VIII students at SMPN 2 Pancarijang. The final results show that student Which Study use videos animation own positive impact compared to with students who learns like usually.